How do Bilateral Investment Treaties work? Evidence from highly regulated industries - Gertz, G (2013)
While much has been written on whether signing bilateral investment treaties (BITs) actually leads to greater inward foreign direct investment (FDI), relatively little attention has been paid to understanding the underlying question of how BITs attract investment. This thesis helps to fill this gap, both theoretically and empirically. It develops a rational choice account of why a government that has signed many BITs will be incentivized to adopt marginally more investor-friendly regulation, a benefit which will be of particular value to one specific group of investors: those in highly regulated industries that do not have easy access to BIT substitutes, most importantly state contracts. Econometric analysis of the effects of BITs on industry-level FDI provides strong support for this model: BITs are associated with an increase in FDI in finance and business services, but not in other industries.